Critical Elements of School Leadership and Human Resource Management: A Systematic Review of Influencing Factors and Development Strategies - Isre, Afrizal Malna (Journal of Idealistic Human Resources, 2025)
Objective: This article aims to identify and synthesize critical elements of school leadership and human resource management (HRM) through a systematic literature review approach. The main focus is on the role of professional development as a capacity-building mechanism in improving leadership effectiveness and strategic HRM practices. Research Design & Methods: This study applied a Systematic Literature Review (SLR) approach by analyzing scientific literature from the past decade through the stages of identification, screening, eligibility, and inclusion, and analyzed using thematic and narrative synthesis. Findings: The review results indicate that continuous professional development—through models such as lesson study, peer coaching, and professional learning communities (PLCs)—has a significant impact on improving teacher capacity, strengthening instructional leadership, and forming distributive leadership. In addition, professional development contributes to teacher retention, talent identification, and learning-based performance evaluation systems. Internal factors such as organizational culture, leadership capacity, and team cohesion, as well as external factors such as national policies and global pressures (e.g., the pandemic and digitalization), also influence the effectiveness of implementation. Implications & Recommendations: These findings have implications for policymakers and school leaders to integrate professional development as a long-term institutional strategy. Key recommendations include the importance of systemic investment in technology-based training, the formation of professional learning communities, and support for instructional leadership at the school level. Contribution & Value Added: This article contributes theoretically to strengthening the relationship between educational leadership and human resource management practices in school settings. The added value of this study lies in the development of a conceptual framework that can serve as a foundation for educational policy development, leadership training planning, and future human resource strengthening strategies.